Evaluating the Association of Calcified Neurocysticercosis and Mesial Temporal Lobe Epilepsy With Hippocampal Sclerosis in a Large Cohort of Patients With Epilepsy - Secchi, Thaís Leite; Brondani, Rosane; Bragatti, José Augusto; Bizzi, Jorge Wladimir Junqueira; Bianchin, Marino Muxfeldt (Frontiers in Neurology, 2022)
Background: Neurocysticercosis (NCC) is an infection of the central nervous system that has been associated with mesial temporal lobe epilepsy with hippocampal sclerosis (MTLE-HS). However, this association has not been completely established. Objective: To evaluate the prevalence of calcified NCC (cNCC), its characteristics and a possible association between cNCC and MTLE-HS in a cohort of 731 patients with epilepsy. Methods: We review findings of 731 patients with epilepsy. From these, 659 had CT-scans and 441 patients had complete neuroimaging with CT-scans and MRI. In these patients, we review the prevalence and characteristic of epilepsy in cNCC and in MTLE-HS patients. Results: Forty-two (6.4%) of the 659 patients studied with CT-scans had cNCC. cNCC lesions were more frequent in women than in men (n=33-78.6% versus n=09-21.4% , respectively; OR=3.64;(95%CI=1.71-7.69);p <0.001). cNCC was more often in patients who developed epilepsy later in life, in older patients, in patients who had a longer history of epilepsy, and in those with a lower educational level. MTLE- HS was observed in 93 (21.1%) of 441 patients that had complete neuroimaging, and 25 (26.9%) of these 93 patients also had cNCC. Calcified NCC was observed in only 17 (4.9%) of the remaining 348 patients that had other types of epilepsy rather than MTLE-HS. Thus, in our cohort, cNCC was more frequently associated with MTLE-HS than with other forms of epilepsy, O.R.=11.90;(95%CI=6.10-23.26); p<0.0001). Conclusions: As expected, in some patients the epilepsy was directly related to cNCC lesional zone, although this was observed in a surprisingly lower number of patients. Also, cNCC lesions were observed in other forms of epilepsy, a finding that could occur only by chance, with epilepsy probably being not related to cNCC at all. In this cohort, cNCC was very commonly associated with MTLE-HS, an observation in agreement with the hypothesis that NCC can contribute to or directly cause MTLE-HS in many patients. Given the broad world prevalence of NCC and the relatively few studies in this field, our findings add more data suggesting a possible and intriguing frequent interplay between NCC and MTLE-HS, two of the most common causes of focal epilepsy worldwide.